Effect evaluation of a comprehensive sexuality education intervention based on socio-emotional learning among adolescents in Jakarta, Indonesia - Todesco, Marina; Breman, Josephine; Haryanto, Naura Nabila; Kok, Gerjo; Massar, Karlijn (Frontiers in Public Health, 2023)
The field of comprehensive sexuality education (CSE) has switched from a focus on adolescents’ health to a more holistic approach, embracing the concept of sexual development with the aim of improving adolescents’ sexual well-being. The growing interest in the link between CSE and socio-emotional learning (SEL) competencies led to the development of the Journey4Life (J4L), a comprehensive sexuality education curriculum based on socio-emotional learning. In the current research, we evaluate the effectiveness of this program on perceived behavioral control, gender equality attitudes, norms, and intentions related to sexual and reproductive health and rights. To this end, we conducted a Cluster Randomized Trial among 14 senior secondary schools in Jakarta, Indonesia. A questionnaire was administered before and after implementation of the J4L program among 16-17 year old pupils; n = 906 completed baseline measurement, n = 771 completed endline measurement. With a final matched sample of N = 466 (65.5% girls) we conducted a mixed model repeated measures ANOVA. Unfortunately, only limited and inconsistent results were found. We found that at endline, girls had stronger positive gender equality attitudes than boys; that overall attitudes towards reporting sexual violence were stronger for girls than for boys. However, contrary to our expectations, respondents had more positive attitudes toward child marriage at baseline than at endline. Inconsistency and non-statistical significance of results limit our ability to draw firm conclusions about the effectiveness of the Journey4Life. We discuss how complex comprehensive sexuality education interventions could best be evaluated, since our study highlights the need for better conceptualization, operationalization and measurement of the interconnection between comprehensive sexuality education and socio-emotional learning.